Considerations in the establishment of weight classes for wrestling and other Olympic combat sports, and measures taken to safeguard the health of these athletes in making weight - Curby, D. G. (International Journal of Wrestling Science, 2024)
Weight classes are used in several Olympic sports. These include the combat sports of wrestling, boxing, judo, taekwondo, and also weight lifting. They are ostensibly used to provide for fair competition, fair opportunity for athletes of various sizes to become champions, and provide safety for the participants. Table 1 lists these sports and the weight classes currently used in competition. One can see that the range of classes for men extends from 51 kg to unlimited, and women from 48 kg to unlimited. There are also differences in the classes used between a sports world championships and the Olympic Games.